1999
DOI: 10.1097/00006454-199910001-00007
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of serious infections in young Gambian infants

Abstract: The most important causes of serious infections in young Gambian infants are Staphylococcus aureus, S. pneumoniae and Salmonella spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 12 publications
3
63
0
1
Order By: Relevance
“…The etiologic findings of the WHO young infant study showed that S. pneumoniae was a significant pathogen, which has driven subsequent maternal vaccination studies and other interventions sponsored by the WHO. 37,38 In our study, S. pneumoniae was also the most common Gram-positive isolate, accounting for 15% of all isolates and was the most important pathogen in the CSF. Neonatal pneumococcal infection is uncommonly reported; a recent review identified only 171 cases of neonatal sepsis owing to S. pneumoniae in a 32-year period.…”
Section: Discussionmentioning
confidence: 55%
“…The etiologic findings of the WHO young infant study showed that S. pneumoniae was a significant pathogen, which has driven subsequent maternal vaccination studies and other interventions sponsored by the WHO. 37,38 In our study, S. pneumoniae was also the most common Gram-positive isolate, accounting for 15% of all isolates and was the most important pathogen in the CSF. Neonatal pneumococcal infection is uncommonly reported; a recent review identified only 171 cases of neonatal sepsis owing to S. pneumoniae in a 32-year period.…”
Section: Discussionmentioning
confidence: 55%
“…One further study reported data that were duplicated by a larger report included in the review (the Gambian component of the multi-country Young Infant Study18) and another19 reported data contained within a more recent study from the same site in Malawi 12. This left 19 studies from 13 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the first week of life, 41.9% of CSF isolates were identified as pneumococcus [13]. A comparable study aiming to identify the aetiology of invasive infection in Gambian infants over the first three months of life reported that 47% of cases of culture-proven meningitis were caused by pneumococcus [14]. Finally, an association has also been demonstrated, in indigenous Australian infants, between the nasopharyngeal pneumococcal carriage and the occurrence of chronic suppurative ear infections [10]; a condition which is also reported with variable prevalence in sub-Saharan Africa and South and East Asia [15].…”
Section: Pneumococcal Carriage and Disease In Early Infancymentioning
confidence: 99%